2018
DOI: 10.1039/c8mh00564h
|View full text |Cite
|
Sign up to set email alerts
|

How to interpret absorption and fluorescence spectra of charge transfer states in an organic solar cell

Abstract: Energetic disorder is crucial to consistently model both absorption and photoluminescence spectra of charge transfer states in organic solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
135
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(141 citation statements)
references
References 60 publications
6
135
0
Order By: Relevance
“…[43] As shown in Figure S9 (Supporting Information), the aggregation domain size, surface roughness, and phase separation effect in the surfaces of the blends are comparable, so we cannot attribute the changes in the photovoltaic behaviors to phase separation. [43] As shown in Figure S9 (Supporting Information), the aggregation domain size, surface roughness, and phase separation effect in the surfaces of the blends are comparable, so we cannot attribute the changes in the photovoltaic behaviors to phase separation.…”
Section: Doi: 101002/aenm201901823mentioning
confidence: 96%
See 1 more Smart Citation
“…[43] As shown in Figure S9 (Supporting Information), the aggregation domain size, surface roughness, and phase separation effect in the surfaces of the blends are comparable, so we cannot attribute the changes in the photovoltaic behaviors to phase separation. [43] As shown in Figure S9 (Supporting Information), the aggregation domain size, surface roughness, and phase separation effect in the surfaces of the blends are comparable, so we cannot attribute the changes in the photovoltaic behaviors to phase separation.…”
Section: Doi: 101002/aenm201901823mentioning
confidence: 96%
“…We carried out AFM and grazing-incidence wide-angle X-ray scattering (GIWAXS) measurements to evaluate the morphology and molecular stacking behavior of the blend films. [43] As shown in Figure S9 (Supporting Information), the aggregation domain size, surface roughness, and phase separation effect in the surfaces of the blends are comparable, so we cannot attribute the changes in the photovoltaic behaviors to phase separation. Based on the 2D patterns obtained by GIWAXS (see Figure S10 in the Supporting Information for details), we can see that before the addition of NRM-1, the blend film has a strong (010) reflection at 1.68 Å −1 in the outof-plane direction corresponding to a π-π stacking distance of 3.74 Å −1 .…”
Section: Reducing Energy Loss (E Loss ) Is Of Critical Importance To mentioning
confidence: 96%
“…In addition, the spectral line shape of the absorption coefficient for hv < E g is indicative of a variety of phenomena such as disorder in amorphous semiconductors and charge transfer absorption in organic semiconductors. Disorder‐induced and charge transfer state absorptions are related to loss mechanisms in organic solar cells, and have been studied extensively to improve solar cell efficiencies . Given the considerable interest in the sub‐bandgap absorption coefficients, sensitive methods of measuring it have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is increasing interest, triggered in particular by the rapid advance in the efficiency of organic solar cells, in better understanding the role of disorder on device performance. [9,12,13,[17][18][19][20][21][22][23][24] In the semiclassical approximation used to derive Equation (3), the CT absorption band is also characterized by a Gaussian distribution with a variance given by Equation (2); [13] the static Molecular dynamics simulations are combined with density functional theory calculations to evaluate the impact of static and dynamic disorders on the energy distribution of charge-transfer (CT) states at donor-acceptor heterojunctions, such as those found in the active layers of organic solar cells. It is shown that each of these two disorder components can be partitioned into contributions related to the energetic disorder of the transport states and to the disorder associated with the hole-electron electrostatic interaction energies.…”
mentioning
confidence: 99%
“…term appearing in the latter is replaced with T 2 σ [14,17,18] 2 1 2 exp 2 nr el 2 T 2 CT a 2 T 2 k V E  π σ λ σ ( ) = − −        …”
mentioning
confidence: 99%